Striking a Trade Deal With President Trump? an Assessment of The Potential of Bilateral Free Trade Agreement (FTA) between the Republic of Indonesia and the United States of America - Yulia Wardani, Ranti; Ziltener, Patrick; ., . (International Journal of Engineering and Technology, 2018)
The US President Donald Trump announced that US would have some bilateral trade consent, as averse to multilateral trade deal such as the Trans-Pacific Partnership (TPP). This research study investigates empirically the economic potential of bilateral Free Trade Agreement (FTA) between Indonesia and the US. The goal is to calculate the maximum savings potential for exporters. The savings potential is defined as duties that have been paid by any WTO exporter countries to another country based on the combination of its exports and the duties thatÂ not reduce at FTA based. The â€œmaximum savingsâ€ is theÂ from the presumption of all export products from the country origin will have zero tariff to enter another country who have an FTA. By using this measurement, country could have ex ante scenarios close to the real calculation tariff without FTA. The data is collected from the UNCOMTRADE and applied tariff rate (ATR) from the WTO. In this research, the level of analysis is the Harmonized System Code (HS Code) 6 digit level. The research findings show that duties of foodstuffs (HS Code 16-24) Indonesian import from the US is the biggest duties compare to other import item products. On the other side the biggest duties export from Indonesia to the U.S is mainly textile (HS Code 50-63). Therefore, the potentialÂ saving from striking a trade deal would be considerable for both side countries. This research study gives more insight about the savings potential for mutual trade bilateral agreement for both countries. Once both countries agree on trade deal, it would encourage more export, raise the competitiveness level for some companies then lead to the economic growth.Â Â